Proceedings of The 8th Pacific Rim International Congress on Advanced Materials and Processing : PRICM 8 - Pacific Rim International Conference on Advanced Materials and Processing 2013 : Waikoloa, Hawaii); Marquis, F. D. S. (Fernand D. S.); Wiley eBooks (Hoboken, New Jersey : Wiley : TMS, 2013)
PRICM-8: Proceedings of the 8th Pacific Rim International Conference on Advanced Materials and Processing.
Microstructure and Properties of Nano-Structured 9CR Oxide Dispersion Strengthened Steels Produced by Atomization and Hot Isostatic PressingRenewable Thermoenergetic Resources in the Pyrometallurgical Copper Production Process; Study on Super Stable All-Solid-State Battery at High Temperature; Study on the Combustion Characteristics and Kinetics of Pulverized Coal in High Oxygen-Enriched Condition; The Preparation and Electrochemical Performances of Al-Si/C Nanocomposite Anode for Lithium Ion Battery; Thermodynamic Evaluation for Formation of MgCu2 from MgH2 and Cu.
"Sponsored by The Chinese Society for Metals (CSM), The Japan Institute of Metals (JIM), The Korean Institute of Metals and Materials (KIM), Materials Australia (MA), and The Minerals, Metals & Materials Society (TMS)."
"Held August 4-9, 2013, at the Hilton Waikoloa Village in Waikoloa, Hawaii, USA."
Includes bibliographical references and indexes.
John Wiley and Sons
Keywords: Materials -- Congresses; Composite materials -- Congresses; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Composite materials; Materials; Composite materials -- Congresses; Manufacturing processes -- Congresses; Materials -- Congresses; Electronic books